2003
DOI: 10.1103/physrevb.68.035324
|View full text |Cite
|
Sign up to set email alerts
|

Short-range electrostatic interactions in atomic-resolution scanning force microscopy on theSi(111)7×7surface

Abstract: A low-temperature scanning force microscope ͑SFM͒ operating in ultrahigh vacuum was used to study the interaction between a sharp but unreactive oxidized silicon tip and a Si͑111͒ 7ϫ7 surface. Weakly corrugated but, nevertheless, atomically resolved images were obtained over a relatively large range of tip-sample distance. The measured short-range interaction potential and image contrast can be explained by an electrostatic interaction that results from a dipole moment induced in the tip by the distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…However, also for larger tip-sample separations, atomic scale contrast has been observed on Si(111)7x7 Ref. [9]. In this work, the authors use a non-reactive oxidized silicon tip and explain that the tip-sample interaction is dominated by the dipole moment induced in the tip due to the surface charge distribution and not by covalent bonding.…”
Section: Introductionmentioning
confidence: 96%
“…However, also for larger tip-sample separations, atomic scale contrast has been observed on Si(111)7x7 Ref. [9]. In this work, the authors use a non-reactive oxidized silicon tip and explain that the tip-sample interaction is dominated by the dipole moment induced in the tip due to the surface charge distribution and not by covalent bonding.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3] The method has first been demonstrated on the ͑111͒ surface of the semiconductor Si, 4,5 and has then been applied to ionic crystalline 6,7 and oxide surfaces. 8,9 It has been shown that identification of atomic species on semiconducting surfaces is possible through a careful study of the force as a function of tip-sample distance.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon tips have been used in several experiments to study alkali halide surfaces [7][8][9][10] or alkali halide thin films on metals [11,12] or molecules on alkali halide surfaces [13,14]. The tips of NC-AFM are often intentionally or spontaneously crashed into the sample during experiments [15]. Theoretical studies suggest that atoms from the sample are transferred onto the tip apex of NCAFMs when in contact with the surface [16].…”
Section: Introductionmentioning
confidence: 99%